Impact of Initial Shunt Type on Cardiac Size and Function in Children With Single Right Ventricle Anomalies Before the Fontan Procedure: The Single Ventricle Reconstruction Extension Trial - FROMMELT, Peter C; GERSTENBERGER, Eric; MCCANDLESS, Rachel T; MERTENS, Luc; PEARSON, Gail D; SPENCER, Carolyn; THACKER, Deepika; WILLIAMS, Ismee A; WONG, Pierre C; NEWBURGER, Jane W; CNOTA, James F; COHEN, Meryl S; et al. (Journal of the American College of Cardiology, 2014)
In children with single right ventricular (RV) anomalies, changes in RV size and function may be influenced by shunt type chosen at the time of the Norwood procedure. The study sought to identify shunt-related differences in echocardiographic findings at 14 months and ≤6 months pre-Fontan in survivors of the Norwood procedure. We compared 2-dimensional and Doppler echocardiographic indices of RV size and function, neo-aortic and tricuspid valve annulus dimensions and function, and aortic size and patency at 14.1 ± 1.2 months and 33.6 ± 9.6 months in subjects randomized to a Norwood procedure using either the modified Blalock-Taussig shunt (MBTS) or right ventricle to pulmonary artery shunt (RVPAS). Acceptable echocardiograms were available at both time points in 240 subjects (114 MBTS, 126 RVPAS). At 14 months, all indices were similar between shunt groups. From the 14-month to pre-Fontan echocardiogram, the MBTS group had stable indexed RV volumes and ejection fraction, while the RVPAS group had increased RV end-systolic volume (p = 0.004) and decreased right ventricular ejection fraction (RVEF) (p = 0.004). From 14 months to pre-Fontan, the treatment groups were similar with respect to decline in indexed neo-aortic valve area, >mild neo-aortic valve regurgitation (<5% at each time), indexed tricuspid valve area, and ≥moderate tricuspid valve regurgitation (<20% at each time). Initial Norwood shunt type influences pre-Fontan RV remodeling during the second and third years of life in survivors with single RV anomalies, with greater RVEF deterioration after RVPAS. Encouragingly, other indices of RV function remain stable before Fontan regardless of shunt type. (Comparison of Two Types of Shunts in Infants with Single Ventricle Defect Undergoing Staged Reconstruction-Pediatric Heart Network; NCT00115934).